Deferiprone, an iron chelator, alleviates platelet hyperactivity in patients with β-thalassaemia/HbE - Ngan Thi Tran; Pranee Sutcharitchan; Jindaporn Janprasit; Ponlapat Rojnuckarin; Noppawan Phumala Morales; Rataya Luechapudiporn (Drugs in Context, 2022)
Background: Hyperfunctional platelets play important roles in thromboembolism in patients with β-thalassaemia/ haemoglobin E (β-thal/HbE). Our previous study revealed ex vivo inhibitory effects of deferiprone on normal platelets. Herein, we aimed to investigate the in vivo effects on platelets in patients with β-thal/HbE.